Does My Neck Make Me Clumsy? A Systematic Review of Clinical and Neurophysiological Studies in Humans - Harman, Samantha C.; Zheng, Zhen; Kendall, Julie C.; Vindigni, Dein; Polus, Barbara I. (Frontiers in Pain Research, 2021)
Introduction: Clumsiness has been described as a symptom associated with neck pain and injury. However, the actuality of this symptom in clinical practice is unclear. The aim of this investigation was to collect definitions and frequency of reports of clumsiness in clinical studies of neck pain/injury, identify objective measures of clumsiness and investigate the association between the neck and objective measures of clumsiness. Methods: Six electronic databases were systematically searched, records identified and assessed including a risk of bias. Heterogeneity in designs of studies prevented pooling of data, so qualitative analysis was undertaken. Results: Eighteen studies were retrieved and assessed; the overall quality of evidence was moderate to high. Eight were prospective cross-sectional studies comparing upper limb sensorimotor task performance and ten were case series involving a healthy cohort only. Clumsiness was defined as a deficit in coordination or impairment of upper limb kinesthesia. All but one of 18 studies found a deterioration in performing upper limb kinesthetic tasks including a healthy cohort where participants were exposed to a natural neck intervention that required the neck to function towards extreme limits. Conclusion: Alterations in neck sensory input occurring as a result of requiring the neck to operate near the end of its functional range in healthy people and in patients with neck pain/injury are associated with reductions in acuity of upper limb kinesthetic sense and deterioration in sensorimotor performance. Understanding the association between the neck and decreased accuracy of upper limb kinesthetic tasks provide pathways for treatment and rehabilitation strategies in managing clumsiness.